Water Flow Measurement-Based Data Acquisition Using Arduino Microcontroller and PLX-DAQ Software - Benriwati Maharmi; Bertanida Widyastomo; Fadhli Palaha (Universitas Ahmad Dahlan, 2022)
The data acquisition for monitoring the water flows in real-time, which is available at any time, is needed for water management purposes. This paper aims to build a prototype of a water flow measurement system in an open channel of a rectangular weir box design using the American Standard Testing and Material (ASTM). This research contribution is a development of a water flow measurement, which can be used as a simulator for studies on measuring water discharge in real cases in the field. More, this instrument is based on the data logger using Arduino, which is designed at a low cost and is easy to use. This water flow equipment can be measured in real-time, so that data information can be directly obtained for analysis. The design of a data acquisition system can display water discharge data in real-time from time to time and allows data storage (data logger) as historical data that can be displayed whenever needed. The Arduino UNO ATMEGA 328 microcontroller was programmed to read the HC-SR04 water level sensor on a distance-based weir box displayed on the LCD. Monitoring and recording of data were displayed on the Parallax Data Acquisition tool (PLX-DAQ) software add-on for Microsoft Excel in real-time. The prototype was able to provide a real simulation of the water flow calculation process until the maximum design capacity of 784,384.87 liters per day. Tests on the overall performance of the water flow measurement system were carried out using flowing water media at 3 different flow conditions based on time. From the average log data of the tests carried out, the deviation of the measurement data against the ASTM calculation theory on average of 0.8 liters/minute. These results were quite good because of the 16,502 liters of water measured. The difference in the calculation results was only 1.003 liters.